Associations between Left Ventricular Cavity Size and Cardiac Function and Overload Determined by Natriuretic Peptide Levels and a Covariance Structure Analysis - Jun Yoshida (Nature Portfolio, 2017)
Abstract The effects of left ventricular (LV) cavity size on cardiac function and overload have not yet been fully elucidated. We performed a covariance structure analysis and drew theoretical path models to clarify the effects of hemodynamic parameters on the stroke volume index (SVI) as a marker of cardiac function and on the plasma B-type natriuretic peptide (BNP) level as a marker of cardiac overload. We simultaneously measured various hemodynamic parameters and the BNP levels during cardiac catheterization in 1,715 inpatients of our institution. The current path models tested the validity of the Frank-Starling law in patients with heart failure using the SVI, the LV end-systolic volume index (LVESVI) and the LV end-diastolic volume index (LVEDVI). Using the BNP levels, the path models clearly demonstrated that LVESVI substantially augmented cardiac overload, whereas LVEDVI palliated this parameter. These volume indices exerted opposite effects on cardiac function and overload. These results advance the understanding of the relationships between LV cavity size and both cardiac function and overload and indicate the increasing importance of LV diastolic volume in heart failure and the utility of LVESVI as an important marker of cardiac remodeling for further relevant studies.